Dynamic analysis on rugby ball kicking parameters - Noor Azam, Nor Afiqah; Ibrahim, Ahmad Imran; Abdul Rahman, Farah Diyana (Solid State Technology, 2020)
Robotic sport has a huge potential to improve sport industry due to its capability and accuracy of repeating motion with controlled parameters. This research focuses on dynamic analysis of kicking a rugby ball in a controlled environment. Optimum angle of attack and initial velocity for the kicking are calculated using kinematic equation as well as conservation of momentum formula. These values are verified using SOLIDWORK finite element analysis simulation software and a simple robotic kicking mechanism in a controlled environment. It is found that the error between theoretical and experimental results is 14 percent error for initial velocity required and 3.25 percent for angle of attack based on 200 trials. The result could be improved by taking additional parameters into consideration, such as the spinning motion of the rugby ball and air resistance during the flight as well as friction inside the robotic mechanism.